Repurposing pentamidine for cancer immunotherapy by targeting the PD1/PD-L1 immune checkpoint - Gu, Tingxuan; Tian, Xueli; Wang, Yuanyuan; Yang, Wenqian; Li, Wenwen; Song, Mengqiu; Zhao, Ran; Wang, Mengqiao; Gao, Quanli; Li, Tiepeng; Zhang, Chengjuan; Kundu, Joydeb Kumar; et al. (Frontiers in Immunology, 2023)
Immunotherapy has emerged as an effective therapeutic approach for several types of cancer. Reinvigoration of tumor-infiltrating lymphocytes-mediated immune attack via the blockade of immune checkpoint markers, such as program cell death-1 (PD1) or its cognate ligand PD-L1 has been the basis of developing clinically effective anticancer therapies. We found pentamidine, an FDA-approved antimicrobial agent, as a small molecule antagonist of PD-L1. Pentamidine enhanced T cell-mediated cytotoxicity against various cancer cells in vitro by increasing the secretion of IFN-γ, TNF-α, perforin and granzyme B in culture medium. Pentamidine caused T cell activation by blocking the PD-1/PD-L1 interaction, the blockade was further verified by binding and SPR assay. In vivo administration of pentamidine attenuated the tumor growth and prolonged survival of tumor-bearing mice in PD-L1 humanized murine tumor cell xenograft model. Histology of tumor tissues showed increased numbers of tumor-infiltrating lymphocytes upon treatment with pentamidine. In brief, our study suggests that pentamidine holds the potential to be repurposed as a novel PD-L1 antagonist that may overcome the limitations of monoclonal antibody therapy and can emerge as a small molecule cancer immunotherapy.